TEMPORAL LINKS BETWEEN ENDOTOXIN ACTIVITY LEVELS AND INTERLEUKIN 6 CONCENTRATIONS IN ABDOMINAL SEPSIS. Issue 4 (October 2015) - Schneider, Christian; Kuppinger, David; Conradi, Sibylle; Heeg, Florian; Hartl, Wolfgang H.
<x xml:space="preserve">Abstract</x> ABSTRACT In severe human peritonitis, the precise pathophysiological importance of endotoxin is controversial. Prognostic and therapeutic studies have yielded conflicting results. The current study wanted to investigate qualitative, quantitative, and temporal associations between blood endotoxin activity (EA) levels and acute inflammatory reactions. We conducted a prospective observational study in 30 patients with intra-abdominal infections who had undergone specific focus therapies (surgical/radiological/pharmaceutical interventions) and who required intensive care therapy. We performed sequential postinterventional measurements of blood EA levels and plasma interleukin 6 (IL-6) concentrations until recurrence or cure. There was no association between daily EA levels and IL-6 concentrations, or daily EA levels and changes in IL-6 concentrations on subsequent days. We found, however, a significant association between EA levels and IL-6 concentrations, when newly changing EA levels were referred to subsequent changes in IL-6 concentrations (P < 0.05). Increasing EA levels were followed by a 90% increase of subsequent IL-6 concentrations during the next 24 to 48 h, whereas decreasing/stable EA levels were associated with slightly decreasing IL-6 concentrations (P < 0.05). Our findings suggest an altered response of the innate immune system because postinterventional EA levels did not vary with concomitant or subsequent inflammatory reactions and because inflammatory responses to newly increasing EA levels were delayed and comparatively small. Still, our results support the concept that endotoxin is a trigger of inflammatory reactions in human peritonitis.